UNDANG-UNDANG CIPTA KERJA DALAM PERSPEKTIF POLITIK HUKUM: STUDI INVESTASI USAHA MIKRO DAN KECIL - Sri Lestari Handayani (2021)
ABSTRACT Economic Enhancement to be built through a healthy and strong investment climate, including for Micro and Small Business. Unfortunately, regulations related to investment for Micro and Small Business do not fully reflect the existence of a fair relationship between medium and large business actors with Micro and small business. This thesis raises 1) issues related to investment for Micro and Small Business barriers in Law Number 20 of 2008, as well as 2) the factors required by a progressive government to develop Investment for Micro and Small Business based on a political law perspective on the implementation Law Number 11 of 2020 of the Job Creation Act. This research uses a literature study method with a normative juridical to statute approach. Based on this analysis, in order to increase the competitiveness of Micro and small business, in implementing Law Number 11 of 2020 on Job Creation on a legal political perspective, it is necessary to have a progressive government strategy, namely by fostering greater morality in business actors, as mandated in the Fifth Precepts of Pancasila. Keywords: investment, Political Law, Progressive government